Low power voltage reference in current mode approach - Low, Qiong Wei. (2012)
Voltage reference is an electronic device that exhibits little dependence on the temperature changes, power supply variations and process parameters. It is an essential building block of many analog circuits and it can be generated by using the weighted sum of voltages of opposite temperature coefficients. In this report, the basics and different implementation approaches of voltage reference are discussed.